COMPARATIVE STUDY OF MEANING EXPANSION AND NARROWING OF QUALITATIVE ADJECTIVES IN ENGLISH AND UZBEK (Journal of Universal Science Research, 2025)
This article discusses the semantic changes of the meaning adjective which includes narrowing and expansion in English and Uzbek languages. Language is the means of forming thoughts and transmitting information to other people. The adjective plays a crucial role in language aspects, which describes a noun. It is natural factor that language changes in over time, so this article studies a comparative analysis of the factor influencing these changes.